The use of force in criminal justice - Hough, Richard M., Senior (Routledge, 2018)
Acknowledgments -- Considering the use of force in criminal justice -- Law and the use of force -- The construction and content of force policies -- The use of less lethal force -- The use of lethal force -- Physiological and psychological considerations in force situations -- Training to use force -- Use of force in law enforcement -- Use of force in corrections -- Force by tactical teams -- Force and special populations -- The future is now -- Index